Answer:
1.
(0,6)
(-1,6)
(3,12)
2.
(0,4)
(-1,6)
Step-by-step explanation:
The rule for the first question is y = 2x + 6
We can substitute the numbers for each equation.
6 = 2(0) + 6
6 = 6
So (0,6) is correct.
4 = 2(-1) + 6
4 = 4
So (-1,4) is correct as well.
-4 = 2(-1) + 6
-4 ≠ 4
(-1,-4) is incorrect.
12 = 2(3) + 6
12 = 12
So this answer is correct as well.
The second question‘s rule is that y = 4 - 2x. So we can substitute the numbers.
2 = 4 - 2(-1)
2 ≠ 6
This is incorrect.
4 = 4 - 2(0)
4 = 4
This answer is correct.
6 = 4 - 2(-1)
6 = 6
This answer is correct as well.
6 = 4 - 2(1)
6 ≠ 2
This answer is incorrect as well.
Sample Response: First, the like terms had to be combined using the lowest common denominator (LCD). Then the subtraction property of equality was used to isolate the variable term. Finally, both sides of the equation were multiplied by the reciprocal of the coefficient to solve for a.
Answer:
I dong kno i need point im so sorry
1.89 * 10^12 is a number written in scientific notation. To write a number in scientific notation, you write a number that is 1 or greater and less than 10, and then multiply it by 10 raised to an integer.
1.89 is the number from 1 to under 10.
12 is the integer exponent of 10.
The calculator writes 1.89 * 10^12, the number in scientific notation, as 1.89E12.
Again, 1.89 is the number from 1 to under 10, and 12 is the exponent. The E shows that the number after it is the exponent.
To write 1.89 * 10^-12, the calculator would write 1.89E-12.
The E stands for the exponent of 10 in scientific notation.